Teaching and learning with virtual teams - Ferris, Sharmila Pixy.; Godar, Susan Hayes 1948-.; Gale Group (Hershey, Penn. Information Science Pub., 2006)
"This book investigates issues around teams in the virtual and hybrid classroom, offering a view of current research and practice on the subject of virtual and collaborative teams in teaching and learning"--Provided by publisher.
From e-learning to learning in virtual teams -- Strategies for effective teaching and learning in virtual teams -- Teams in action : international collaboration -- Teams and technology.
Electronic reproduction.
Keywords: Group work in education; Team learning approach in education; Teaching teams; Distance education -- Computer-assisted instruction; Electronic books